2018
DOI: 10.3390/coatings8040144
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Self-healing Superhydrophobic Surfaces from Water-Soluble Polymer Suspensions Free of Inorganic Particles through Polymer Thermal Reconstruction

Abstract: Self-healing superhydrophobic surfaces have been fabricated by casting and drying water-soluble amphiphilic polymer suspensions at room temperature through thermal reconstruction. When compared with previous methods, this approach exploits modified natural hierarchical microstructures from wood instead of artificially constructing them for superhydrophobic morphology, which involves neither organic solvent nor inorganic particles nor complex procedures. The obtained superhydrophobic surface has acceptable resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…For example, when the wood surface sprayed with perfluorooctyltriethoxysilane (KH1322)/silica composite suspension was subjected to mechanical wear, it could be restored to its self-healing ability by respraying a fluoroalkylsilane/silica composite suspension. 78,79…”
Section: Synthesis Strategiesmentioning
confidence: 99%
“…For example, when the wood surface sprayed with perfluorooctyltriethoxysilane (KH1322)/silica composite suspension was subjected to mechanical wear, it could be restored to its self-healing ability by respraying a fluoroalkylsilane/silica composite suspension. 78,79…”
Section: Synthesis Strategiesmentioning
confidence: 99%
“…It has been reported that hydrophobic wood can have improved water resistance and mildew inhibition, but the anti-mildew effect was not significant [32]. Although a hydrophobic surface can reduce the adherence of bacteria and water, it does not have the function of sterilization, leading to poor anti-mildew properties for hydrophobic modified bamboo [31,32]. It is interesting to investigate the synergistic effect of hydrophobic surface with antimicrobial agents, because it will afford bamboo good resistance to both water absorption and microbial degradation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that hydrophobic surfaces can inhibit the adherence of bacteria, decreasing the incidence of infection [30,31]. It has been reported that hydrophobic wood can have improved water resistance and mildew inhibition, but the anti-mildew effect was not significant [32]. Although a hydrophobic surface can reduce the adherence of bacteria and water, it does not have the function of sterilization, leading to poor anti-mildew properties for hydrophobic modified bamboo [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The main weak point of a roughened surface is the vulnerability of the texture to mechanical damage. This can be overcome by the right choice of durable raw materials (e.g., metals [65], brittle inorganics [68]) or by utilizing self-healing behaviour to regain the damaged roughness [69][70][71][72].…”
Section: Utilization and Elaboration Of Surface Texturementioning
confidence: 99%